Genetic relatedness and population structure within the public Argentinean collection of maize inbred lines - Olmos, Sofía Eugenia (2014)
Genetic diversity of an Argentinean public temperate inbred maize collection has not been previously assessed. This collection includes mainly locally developed orange flint germplasm and a group of temperate inbred lines introduced from the US or derived from selection of crosses to genetic stocks from other countries, providing representativeness of exotic gene pools. To establish heterotic groups and patterns for breeding purposes and to assess genetic structure and relatedness for association-mapping studies, a public panel of a 103 maize inbreds was characterized using 50 microsatellite markers and pedigree information. By means of clustering-based and model-based methods the flint germplasm collection was split into two subpopulations that were separated from the BSSS-BS13-related lines. Relatedness estimates with coancestry and kinship coefficients provided additional information in the case of structured mixed membership of some germplasm. These three main subpopulations were in agreement with prior pedigree records. Allele diversity was high and sufficient to give major, minor and specific allele profiles to characterize inbred lines. Convenience of the use of minor allele frequency for structure and relatedness assessment is also discussed. In addition, molecular characterization provided useful information to elucidate inbred ancestry origins of germplasm with unknown pedigree records and to group them into known heterotic groups to define heterotic patterns.